Effect of different soil types on growth and production of Napier-4 at the Regional Station of BLRI - Islam, Mohammed Sirajul; Sarker, Nathu Ram; Habib, MA; Ali, Md Yousuf; Yeasmin, Tahera (Asian Journal of Medical and Biological Research, 2017)
A comparative agronomical trial was conducted to know the effect of two different soil types on growth and production performance of BLRI Napier-4 fodder production at BLRI regional station, Baghabari, Shahzadpur, Sirajganj. Soil components are the determinant factors for growing any crops or fodders. Soil samples from sandy soil and normal soil (loamy) were analazed for soil pH, nitrogen, organic matter, salinity, Ca, K, S, Zn, Pb, Co, Mg, Fe etc. at the Central Laboratory of Soil Resource Development Institute (SRDI), Dhaka. Data were recorded on plant height, stem length, leaf length, number of leaf per stem, number of till per hill, yield per hill and total biomass yield per plot. Plant height, stem length and leaf length produced in normal soil were significantly higher (p<0.001) than those produced in sandy soil. Irrespective of soil type, the plant height, stem length, leaf length, yield per hill and biomass yield per plot produced in second harvest were significantly higher (p<0.001) than those produced in first harvest. But, number of leaf per stem and number of till per hill did not differ significantly (p>0.05) between two cuttings. It can be concluded from the present findings that BLRI Napier-4 cultivar may be produced in the sandy soil. Asian J. Med. Biol. Res. June 2017, 3(2): 182-185